Impacts of Various Nutraceutical Milk Replacer Supplements on the Health and Performance of High-Risk Holstein Calves - Davis, Emily M.; Liang, Yu; Batchelder, Tyler A.; Sellers, Matthew D.; Ballou, Michael A. (Frontiers in Animal Science, 2022)
The objectives of this study were to determine the impacts of supplementing nutraceuticals in milk replacer including: a blend of probiotics, β-glucan, mannanoligosaccharide, or a non-immunoglobulin extract from colostrum on the performance and health of high-risk calves and to determine carry-over effects into the immediate post-weaned period. One hundred bull calves were acquired within 24 h of birth and randomly assigned to 1 of 5 treatments added to milk replacer only: (1) Control (CON), no additive; (2) Immu-PRIME (ImmPr), 1.5 g/d ImmPr first 3 d only (Sterling Technology, Brookings, SD); (3) Beta glucan (BG), 1 g/d BG extract (ImmuOligo, Irvine, CA); (4) Mannanoligosaccharide + Bacillus subtilis (MOS+Bs), 3 g/d CEREVIDA EXCELL-M + 4 x 109 CFU/d Bacillus subtilis (MB Nutritional Sciences, Lubbock, TX); and (5) PROVIDA CALF (PRO), proprietary blend of 2 x 109 CFU/d of a Lactobacillus casei and an Enterococcus faecium + 2 x 109 CFU/d Saccharomyces cerevisiae (MB Nutritional Sciences, Lubbock, TX). Calves were weaned at d 56, commingled, and treatment carry-over effects evaluated through d 84. Starter intake was measured daily and BW weekly. Peripheral blood samples were collected on d 1, 3, 7, 14, 21, 42, 56, and 84 and analyzed for hematology and haptoglobin concentrations. Polymorphonuclear leukocyte (PMNL) function was assessed through L-selectin expression along with phagocytic and oxidative burst activities against Escherichia coli. Data were analyzed using Proc Mixed in SAS (SAS 9.4, Cary, NC). The BG calves consumed the most starter from d 1 to 28 and pre-weaned average daily gain (ADG) was greater for both the PRO and BG. There was a tendency for BG, MOS+Bs, and PRO to have reduced haptoglobin throughout the study. Leukocyte, neutrophil, and lymphocyte counts were reduced among MOS+Bs calves, whereas BG calves tended to have the greatest neutrophil:lymphocyte ratio. L-selectin expression was reduced among BG calves and may be attributed to a decrease in neutrophil stimulation. Oxidative burst function for PMNL was reduced among BG and PRO treatments, suggesting a decreased need for neutrophil function. Supplementing BG, MOS+Bs, and PRO all influenced performance and health of high-risk calves, but mechanistically appear to be different.